The Affordable Care Act and assisted reproductive technology use. (22nd December 2015) - Stapleton, Patricia; Skinner, Daniel
Abstract : The Affordable Care Act (ACA) has prompted numerous gender and sexuality controversies. We describe and analyze those involving assisted reproductive technologies (ART). ART in the United States has been regulated in piecemeal fashion, with oversight primarily by individual states. While leaving state authority largely intact, the ACA federalized key practices by establishing essential health benefits (EHBs) that regulate insurance markets and prohibit insurance-coverage denials based on pre-existing conditions. Whatever their intentions, the ACA's drafters thus put infertility in a subtly provocative new light clinically, financially, normatively, politically, and culturally. With particular attention to normative and political dynamics embedded in plausible regulatory trajectories, we review—and attempt to preview —the ACA's effects on infertility-related delivery of health services, on ART utilization, and on reproductive medicine as a factor in American society.